Size, Age and the Growth of Firms: New Evidence from Quantile Regressions - Roberta Distante; Ivan Petrella; Emiliano Santoro (Fondazione Eni Enrico Mattei (FEEM), 2014)
The nexus between firm growth, size and age in U.S. manufacturing is examined through the lens of quantile regression models. A number of interesting features are unveiled that linear frameworks could not detect. Size pushes both low and high performing firms towards the median rate of growth, while age is never advantageous, and more so as firms grow faster.
Keywords: C14; L1; 330; Firm Growth; Size; Age; Conditional Quantile